Iceland : Advancing Tax Reform and the Taxation of Natural Resources. (IMF Staff Country Reports; Country Report ;, 2011)
This study focused on environmental tax measures, and on allocation, pricing, and taxation of Iceland's major hydropower and geothermal resources. Measures to secure the tax base for the corporate income tax (CIT) are proposed. Taxation of the financial sector can be improved by a number of measures. The measures that increase fiscal levies on energy-intensive industries should be avoided. The proposals in this paper aim at efficiency and equity in the tax system rather than revenue growth.